THE APPLICATION OF GOVERNMENTAL ACCOUNTING PRINCIPLES TO PRACTICE. - Frisbee, Ira N. (The Accounting Review, 1939)
The article presents a discussion on the application of accounting principles to governmental-accounting practice in the U.S. Problems of governmental accounting may be divided into three groups, first are problems in accounting for transactions of the Federal government and its agencies; second, problems in accounting for affairs of the several states; third, municipal accounting problems and those of other political subdivisions of The U.S. states, such as counties and districts. This article will confine itself to the application of accounting principles to practice only in municipalities and other political subdivisions of states. Fifteen such principles have been set forth by the National Committee on Municipal Accounting as recommendations or suggestions to be followed as a guide in establishing governmental accounting systems. The article concludes that emphasis must be given to the human or personal difficulties involved in making changes in governmental accounts. In order to install a uniform accounting system, it is essential that the legislative body and, at least, the major executives of the city be in sympathy with the project. without cooperation in the budgeting, purchasing, departmental reporting, and even in the departmentalizing of the city, it is difficult to install a system which is based upon the recommended principles.